2019
DOI: 10.1007/s10652-019-09720-x
|View full text |Cite
|
Sign up to set email alerts
|

Velocity distribution in open channel flow with spatially distributed roughness

Abstract: A numerical procedure is proposed to estimate the velocity distribution in open channel flow, for engineering applications. A method based on the mixing length model and subdivision of the wetted surface, is modified to easily integrate a lateral distribution of roughness. Several friction models for vegetated or rough flows can be added, two of which have been tested. The numerical procedure was developed with a commercial software (Matlab) to ensure fast computation and possible coupling with 1D hydraulic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Against this background, the estimation of bed shear stress using this method has three main issues: (i) small errors in the velocity distribution affect isovelocity curves and could have a great effect when calculating bed shear stress since the geometry of the rays defines the control volume; (ii) it requires analyzing velocity distribution over the full section to compute bed shear stress at any point along the wetted perimeter, where the relation among velocity and shear stress is mainly local; and (iii) the shear stress along the water-air interface is not considered in the momentum balance. Additionally, the eddy viscosity in the model by Cassan et al [18] increases up to free surface without setting a maximum value, contrary to what is observed in reality.…”
Section: Introductioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Against this background, the estimation of bed shear stress using this method has three main issues: (i) small errors in the velocity distribution affect isovelocity curves and could have a great effect when calculating bed shear stress since the geometry of the rays defines the control volume; (ii) it requires analyzing velocity distribution over the full section to compute bed shear stress at any point along the wetted perimeter, where the relation among velocity and shear stress is mainly local; and (iii) the shear stress along the water-air interface is not considered in the momentum balance. Additionally, the eddy viscosity in the model by Cassan et al [18] increases up to free surface without setting a maximum value, contrary to what is observed in reality.…”
Section: Introductioncontrasting
confidence: 57%
“…Additionally, Kean and Smith [11] found that the eddy viscosity increases along each ray until it reaches a maximum value to be calibrated. However, in Cassan et al [18], the eddy viscosity increases as it approaches the free surface without reaching a maximum value. For simplicity reasons and avoiding the use of adjustment parameters, a shear stress-independent function similar to Equation ( 5) is considered hereinafter for the eddy viscosity distribution along the rays, increasing until it reaches its maximum value of ν t,max = κu * h/4 at d = h/2, and then remaining constant from that point to the end of the ray, at the point where maximum velocity is located.…”
Section: Eddy Viscositymentioning
confidence: 92%
See 2 more Smart Citations
“…Both d-type and k-type roughness boundary conditions are discussed, including the secondary flow motion. Cassan et al [8] analyse the effect of spatial roughness distribution along fixed boundaries. Based upon a simplified solution of the Navier-Stokes equations, the boundary shear stress distribution may be derived along the wetted perimeter.…”
Section: Special Issue Contentsmentioning
confidence: 99%